DIGITAL ECONOMY CHALLENGE: HIDDEN EXPLOITATION OF CHILD LABOUR THROUGH THE USE OF DIGITAL DEVICES - Sukma, Weni Lidya; Ruslan, Kadir (Journal of Central Banking Law and Institutions, 2025)
This study focuses on child labour working hours for children aged 5-14, utilising National Labor Force Survey (Sakernas) data collected in August 2023. Specifically, it examines the impact ofthe use of digital devices on the working hours for child labourers. Applying ordinary least squares (OLS) regression to the data, our findings indicate that digital tools increase working hours by 1.12 per week, even after controlling for various explanatory variables. This effect is particularly pronounced for child workers aged 12-14. Factors such as low levels of education and employment in the service sector were identified as contributors to extended working hours for child labour. However, digital tools and the internet have become essential for everyone, including children. Therefore, reducing child labour and working hours requires a multifaceted approach involving strengthening regulations, restoring disrupted children’s education, and enhancing overall well-being.